National E-cigarette Survey (NECS) 2016 in Malaysia method and population characteristics - Ab Rahman, Jamalludin; Nik Mohamed, Mohamad Haniki; Kartiwi, Mira; Ab Rahman, Norny Syafinaz; Draman, Samsul; Mohd Yusoff, Muhammad Fadhli; Arif, Tahir (Malaysia Medical Association, 2017)
E-cigarette and vape (ECV) use has become a worldwide phenomenon since 2010. This study aims to determine the prevalence of ever user, current user and factors associated with ECV use among Malaysian adults. This will provide evidence for policy makers to formulate appropriate measures towards regulation of ECV in Malaysia and can become a reference for other similar countries. Method: Complex sampling design was used to represent 19 million of Malaysian adult household. Samples were stratified by states and urbanity. Sampling units were districts, enumeration blocks and living quarters. All adults from the selected houses were invited to participate in this survey. Analysis was done using sampling weight and complex sampling analysis. Results: A total of 4,288 individual responded in this survey. Majority of the respondents were at 25-44 years of age group (44%), completed at least secondary level of education (69%), of Malay ethnicity (73%), Muslim (79%) and married (68%). Male and female were equally represented. Seventy two percent of the respondents were from the urban residential area (n=2,123). The prevalence of current ECV users was 3.2%, with an estimated number of 602,122 in the population. The prevalence was 3.3% and 2.9% in urban and rural respectively. ECV users were common among 18-24 years old, male and those with tertiary level education.This study able to represent Malaysia and results can be used to guide healthcare managers to manage e-cigarette use in the country